Physico-chemical, mechanical and antibacterial properties of the boron modified biphasic larnite/bredigite cements for potential use in dentistry. Issue 4 (15th February 2023) - Sopcak, T.; Medvecky, L.; Jevinova, P.; Giretova, M.; Mahun, A.; Kobera, L.; Stulajterova, R.; Kromka, F.; Girman, V.; Balaz, M.
Abstract: In recent years, there has been a growing interest in developing more reactive calcium silicate cements (CSCs) with superior bioactivity, self-setting properties and mechanical strength, allowing them to be used for various dental applications. In this study, we have produced a biphasic larnite/bredigite calcium magnesium silicate cement (CaMgSi) by the low-temperature sol-gel method and calcination of xerogels at 700 °C. The effect of boron (B) incorporation (0.25 and 0.5 mol) on the structural and physico-chemical properties of CaMgSi and boron-modified CaMgSi/0.25B and CaMgSi/0.5B cements was evaluated using various characterization techniques, such as X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning and transmission electron microscopy (SEM/TEM) and solid-state NMR spectroscopy (ssNMR). The results showed that with the increasing boron content, the cements hydration, self-setting and mechanical properties were improved. Hence, the final setting time of CaMgSi/0.5B cement decreased from 30 (undoped cement) to 19 min, while the compressive (CST) and diametral tensile strengths (DTS) increased almost twice to the highest values of 85 ± 9 MPa and 8.8 ± 1 MPa, respectively. The in-vitro bioactivity and degradation of cements were examined in simulated body fluid (SBF) solution during 8 weeks of soaking. Interestingly, the prevalence of calcite and aragonite crystals of various morphologies was observed on all cement surfaces, whereas a plate-like particles of precipitated calcium phosphate layer were found only in the boron-modified CaMgSi/0.25B and CaMgSi/0.5B cements. In addition, a very good antibacterial activity of the cement suspensions was revealed against all the tested bacteria, i.e. Staphylococcus aureus, Escherichia coli and Enterococcus faecalis, showing a promising result for potential use in dentistry.